Intersection of identities. Food, role, and the African–American pastor() - Harmon, Brook E. (2013)
African–American pastors can foster health-related innovations as gatekeepers and advocates within their churches. Personal experiences with food and health likely influence their support of such programs. Identities or meanings attached to societal roles have been shown to motivate individuals’ attitudes and behaviors. Understanding role and eating identities of African–American pastors may have important implications for participation in faith-based health promotion programs. This study aimed to describe the eating and pastoral identities of African–American pastors, explore intersections between these identities, and highlight implications for nutrition programs. In-depth interviews with 30 African–American pastors were audio-recorded and transcribed verbatim. Data were analyzed using theory-guided and grounded-theory approaches. Pastors described affinity across one or more dimensions including healthy, picky, meat, and over-eater identities. In describing themselves as pastors, the dimensions pastor’s heart, teacher, motivator, and role model emerged. Pastors who described themselves as healthy eaters were more likely to see themselves as role models. Pastors with healthier eating identities and more complex pastoral identities described greater support for health programming while unhealthy, picky, and over-eaters did not. These findings provide guidance for understanding eating and role identities among pastors and should be considered when designing and implementing faith-based programs.